Suprathel-acetic acid matrix versus acticoat and aquacel as an antiseptic dressing: an in vitro study - Ryssel, Henning; Germann, Günter; Riedel, Katrin; Reichenberger, Matthias; Hellmich, Susanne; Kloeters, Oliver (Annals of plastic surgery, 2010)
Background: - The treatment of burn wounds is still a challenge regarding the management of antiseptic wound conditioning. Especially, in the United States, silver-containing dressings, such as Acticoat and Aquacel are frequently used. Because silver-containing dressings have well-known drawbacks such as an antimicrobial lack against Pseudomonas aeruginosa, we sought to develop an alternative dressing method. In previous studies, we could demonstrate the excellent antiseptic properties of acetic acid against common burn unit germs, and in another study, the feasibility and suitability of a Suprathel-acetic acid matrix as an antiseptic dressing. - Materials and Methods: - This study was designed to test the in vitro antimicrobial effect of a Suprathel-acetic acid matrix versus Acticoat and Aquacel. To cover the typical bacterial spectrum of a burn unit, the following Gram-negative and Gram-positive bacteria strains were tested: Escherichia coli, extended-spectrum beta-lactamase-positive Klebsiella pneumoniae, P. aeruginosa, Acinetobacter baumannii, Enterococcus faecalis, and methicillin-resistant Staphylococcus aureus. - Results: - The tests showed an excellent bactericidal effect of the Suprathel-acetic acid matrix particularly with problematic Gram-negative bacteria such as Proteus vulgaris, P. aeruginosa, and Acinetobacter baumannii. The efficiency was superior to that of Acicoat and Aquacel. - Conclusions: - Our results support the notion, that the Suprathel-acetic acid matrix has an excellent bactericidal effect and therefore seems to be suitable as a local antiseptic agent in the treatment of burn wounds.